Unpacking the African continental free trade area: A glossary - International Trade Centre (ITC) (International Trade Centre (ITC), 2023)
This glossary is the first edition of legal and other terms that micro, small and medium enterprises (MSMEs) will encounter while trading under the African Continental Free Trade Area (AfCFTA). The aim of the glossary is to help users understand legal, commercial and customs terms found in the AfCFTA Agreement as it has been crafted with inputs and guidance from the African private sector, including MSMEs, women and youth entrepreneurs, and business support institutions striving to improve the African business environment.
Keywords: AfCFTA; Glossaire; Lexique; ZLECAf

Justice civile amiable, justice pénale négociée... vers une justice consensuelle ? (Ecole Nationale de la Magistrature, 2023)
Keywords: Conciliation; Conciliação (processo civil); Consentement; Justice amiable; Justice négociée; Médiation; Politique de l'amiable; Procédure pénale

The Concise Encyclopedia of Business Ethics - MacDonald, Chris; Marcoux, Alexei (Toronto Metropolitan University, 2023)
The authors’ aim in writing The Concise Encyclopedia of Business Ethics (CEBE) was to provide readers with a useful, concise overview of key issues in business ethics. Our aim is not to be exhaustive, but to provide key definitions, main areas of controversy, and pointers for further reading. It is hoped that it will provide a useful reference guide for students, as well as a starting point for scholars in adjacent fields. Our commitment to sticking to what we consider to be essential topics inevitably means that some readers will find that we have left out what they take to be important topics. For the most part, we stand by our editorial choices. However, as a digital document, it is possible that the CEBE will change and grow slightly over the coming years. Readers are free to provide feedback and suggestions by emailing the authors jointly at editors@bejr.org

Les promesses des technologies au service du commerce: Politiques visant à tirer parti de la numérisation du commerce - Organisation mondiale du commerce (WTO, 2023)
Les promesses des technologies au service du commerce – l'ensemble de technologies grâce auxquelles le commerce mondial peut devenir plus efficace, plus inclusif et plus durable – sont nombreuses, depuis la facilitation des échanges jusqu'aux gains d'efficacité et à la réduction des coûts en passant par l'amélioration de la transparence et de la résilience des chaînes d'approvisionnement. Certes, l'innovation technologique existe, mais le plus grand défi en ce qui concerne l'adoption des technologies au service du commerce à l'échelle mondiale consistera à mettre en place une coordination internationale des politiques. Les accords commerciaux peuvent jouer un rôle primordial. En dépit des efforts actuels en vue d'introduire des dispositions relatives au commerce numérique, il subsiste nombre de possibilités inexploitées et de politiques inexplorées. Cette publication conjointe du Forum économique mondial et de l'OMC examine de quelle façon les accords commerciaux pourraient être mobilisés pour faire progresser l'adoption des technologies numériques et la numérisation du commerce.
Keywords: Accords régionaux de commerce; Commerce électronique; Technologies de l'information

Les chaînes d’approvisionnement mondiales à forte intensité technologique : le potentiel de l’Afrique - Conférence des Nations Unies sur le Commerce et le Développement (CNUCED) (Nations Unies, 2023)
Rapport sur le développement économique en Afrique 2023

The Potential of Africa to capture technology-intensive global supply chains - United Nations Conference on Trade and Development (United Nations, 2023)
Economic Development in Africa Report 2023

Corporate Finance, Governance, and Social Responsibility - Gherghina, Ştefan Cristian (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This reprint covers 27 papers published in the Special Issue entitled Corporate Finance, Governance, and Social Responsibility, which examines several topics related to corporate finance, financial modeling, corporate governance, and corporate social responsibility. Corporate finance-related articles (Anton and Afloarei Nucu, 2021; Bae et al., 2023; Kedzior et al., 2020; Lts and Lukason, 2022; Miglo, 2020; Mihail et al., 2021; Mota and Moreira, 2023; Tsolas, 2021; Tudose et al., 2021; and Wen et al., 2021) focus on the drivers of the capital structure and firm performance, the effect of working capital management on profitability, and the link between derivative use and profitability. Regarding financial modeling, stock market volatility was explored during COVID-19 (Gherghina et al., 2021). Corporate governance studies (Aluchna and Kuszewski, 2020; Ararat et al., 2021; Ding and Chea, 2021; Kjrland et al., 2020; Loureno et al., 2021; Lukason and Camacho-Miano, 2020; Maier and Yurtoglu, 2022; Mihail and Dumitrescu, 2021; Mihail et al., 2022; Mihail and Micu, 2021; and Pourmansouri et al., 2022) examine the effect of corporate governance compliance practices, board attributes, or employee stock option plans on bankruptcy risk, performance, firm value, or earnings management. Regarding CSR (Bozos et al., 2022; Rossi et al., 2021; Saeed and Sroufe, 2021; Singh and Hong, 2023; and Tseng and Shih, 2022), the research focuses on how CSR affects financial performance, risk management, or analyst profits estimates.
Keywords: CSR; Corporate Finance; Financial performance

Third Party Funding in International Arbitration: A Critical Appraisal and Pragmatic Proposal - Sweify, Mohamed (Edward Elgar Publishing, 2023)
The author of Third Party Funding in International Arbitration challenges the structural inconsistencies of the current practices of arbitration funding by arguing that third party funding should be a forum of justice, rather than a forum of profit. The author introduces a new methodology with an alternative way of structuring third party funding to solve a set of practical problems generated by the risk of claim control by the funder.
Keywords: ACCESS TO JUSTICE; Arbitrage; Arbitral justice; Arbitration; Claim control; Dispute outcome; Financement; Funders; Third Party Funding; Tiers

Cadre de convergence réglementaire du transport routier et sa stratégie d’application sous-régionale en Afrique de l’Ouest - Conférence des Nations Unies sur le Commerce et le Développement (CNUCED) (Nations Unies, 2023)

Des mots appelés à la barre : vocabulaire du droit - Le Barreau du Québec et ses avocats (Office québécois de la langue française, 2023)

Le terrorisme au Benin: perceptions, actions et perspectives / Sous la direction de Thierry S. Bidouzo et Expédit B. Ologou ; avec les contributions de Vincent Afouda Agué, Estelle Djanato, Emmanuel Odilon Koukoubou (Friedrich-Ebert-Stiftung Bénin, 2023)
Longtemps considéré comme un havre de paix, le Bénin se retrouve pris au piège de la menace terroriste, subissant des attaques depuis décembre 2021. Les groupes armés venus du Sahel frappent de plus en plus les pays côtiers du golfe de Guinée et provoquent l'exacerbation des dynamiques conflictuelles dans la région. Le fléau du terrorisme et de l'extrémisme violent prend une grande ampleur notamment dans les zones septentrionales du Bénin, où les attaques prennent de plus en plus des formes de violences extrêmes. La vie quotidienne des populations, la quiétude, la cohésion sociale sont alors hypothéquées, car otages des groupes armés terroristes. Comme face à tout péril réel, imminent ou lointain, des interrogations, des perceptions, des résolutions, des attentes ne sauraient manquer dans les pensées des Béninois. La présente étude tente une restitution de ces pensées citoyennes sur la menace terroriste.

Entreprises et droits de l'Homme : Protéger, respecter, réparer - Commission nationale consultative des droits de l'homme (La documentation française, 2023)
Le rapport vise à analyser les développements normatifs et les politiques menées par la France sur la thématique Entreprises et droits de l’Homme depuis l’adoption de son plan national d’action, aux niveaux international (première partie), régional (deuxième partie) et national (troisième partie). La CNCDH formule 145 recommandations, dont 20 prioritaires, afin d’encourager la France à redoubler d’ambition pour le respect et la protection des droits de l’Homme dans le contexte des activités des entreprises. Il s’agit d’améliorer la mise en œuvre des cadres normatifs et mécanismes existants, de soutenir de futurs développements normatifs qui constituent un nivellement par le haut et de lever les obstacles à l’accès aux voies de recours et à la réparation, pour s’assurer qu’en cas de violations des droits de l’Homme commises, directement ou indirectement, par les entreprises, leur responsabilité puisse être engagée.

Redesigning Protection for Consumer Autonomy: The case-study of dark patterns in European private law - Guerra, Giorgia (FrancoAngeli, 2023)
European legal protection of consumer autonomy has been significantly changed in the digital environment, where algorithm-driven systems perform everything. This book focuses on protecting consumer autonomy facing the pervasive and global phenomenon of dark patterns: the expression includes various tactics that manipulate consumers by altering online choice architecture to thwart user preferences for objectionable ends. Overloading, skipping, stirring, hindering, and flicking are examples. Moving from the perspective that the sole traditional information approach is ineffective in protecting autonomy, the adopted methodology considers the multiple concerns revolving around the tight combination of transparent information and fair digital architectural design. Consequently, the comparative study of the new suitable regulatory directions arises across different legal fields, including data protection, consumer, and competition law. The relationship between deceptive designs, the nature of human-digital architecture interaction, and the techno-legal paradigms emphasises which future changes in European private law could integrate legal rules into fair designs to protect digital consumer autonomy effectively. Specific importance will be attributed to the functionality of comparative methodology to include non-legal essential insights (e.g. behavioural, informatic elements) into pragmatic and global regulatory paths and models.
Accepted: 2024-02-06T15:32:18Z
Keywords: Autonomy; Consumer law; Dark Patterns; Data protection law; Design regulation; Digital law; European private law

Effective Conflict Management - International Chamber of Commerce (ICC DRS Publications, 2023)

Transnationale Verträge im nationalen Recht: Theorie und Dogmatik transnationaler Ordnungsstrukturen am Beispiel von Musterverträgen im Finanzbereich - Kindt, Torsten (Mohr Siebeck, 2023)
Weltweit vereinheitlichte Musterverträge bestimmen die Vertragsgestaltung im grenzüberschreitenden Finanzverkehr. Diese Musterverträge werden von privaten Organisationen wie der International Chamber of Commerce (ICC), der Loan Market Association (LMA) und der International Swaps and Derivatives Association (ISDA) geschaffen. Torsten Kindt zeigt, dass auf Grundlage der Muster ein bereichsspezifisches transnationales Vertragsrecht entsteht, das jedoch auf vielfältige Weise mit dem staatlichen Recht verwoben bleibt. Er entwickelt Leitlinien für einen responsiven Umgang mit musterbasierten transnationalen Verträgen im staatlichen Kollisions-, Vertrags- und Internationalen Zivilverfahrensrecht, die auch über den Finanzbereich hinaus zu einem produktiven Zusammenwirken privater und staatlicher Ordnung beitragen können.
Keywords: ADR; Alternative dispute resolution; Arbitrage; Arbitragem; Arbitration; Bankruptcy; Civil Law; Dispute resolution; Insolvency; Litigation; MARD; Mediación; Mediation; Mediação; Médiation; Negotiation

The Law Applicable to Security Interests in Intermediated Securities Under OHADA Law - Monsenepwo Mwakwaye, Justin (Mohr Siebeck, 2023)
In recent decades, the technical handling of custody business in the OHADA region has undergone a lasting change. There has been a shift from a direct to an indirect holding system, in which the interests of an investor in respect of the underlying securities are recorded in the books of an intermediary (such as a bank or a securities firm). Under the law of all states within the OHADA region, the traditional conflict of laws rule for determining the enforceability of a securities pledge that occurs in the indirect holding system is the lex rei sitae (or the lex cartae sitae or the lex situs ) rule. However, the traditional lex rei sitae rule cannot be appropriately applied to a system where the dematerialised securities are held through multiple layers of intermediaries located in different jurisdictions. Yet, until the intermediated system and the collateralisation of intermediated securities in the OHADA region will continue to operate in somewhat legally murky waters, leading to more instability in the financial markets. Therefore, Justin Monsenepwo aims to find an appropriate and consistent approach that reflects the reality of the indirect holding system in the OHADA region. “This publication is essential reading for policy makers, academics, market participants, and legal practitioners in the OHADA region and beyond. I am convinced that its in-depth analysis of OHADA’s substantive and conflict of laws rules will go a long way in filling the gap in this area and encouraging further development in the future.” Christophe Bernasconi, Secretary General of the „Hague Conference on Private International Law“ – HCCH in the foreword
Keywords: Commercial; Commercial law; Comparative; Comparative law; Competencia; Competition law; Conflict of laws; Law; Private international law

Guide de la prévention des difficultés des entrprises - Mouvement des entreprises de France (MEDEF, 2023)

Intellectual Property Law in Africa: Harmonising Administration and Policy - Ncube, Caroline B. (Taylor & Francis, 2023)
Examining the harmonisation of Intellectual Property policy, law and administration in Africa, this book evaluates the effectiveness of efforts to establish continental Intellectual Property institutions and frameworks. It also considers sub-regional initiatives led by the regional economic communities and the regional Intellectual Property organisations, focusing on relevant protocols and agreements that address Intellectual Property as well as the implementing institutions. The book assesses the progress of such initiatives with particular reference to the current socio-economic status of African states. It argues that that harmonisation initiatives need to be crafted in a way that is supportive of the developmental goals of African states and advocates for due consideration of individual states’ unique conditions and aspirations. This book will be of great relevance to scholars and policy makers with an interest in Intellectual Property law and its harmonisation in Africa.
Accepted: 2023-06-22T09:36:20Z
Keywords: Africa; Droit (harmonisation); Intellectual property; Public interest; TRIPs; governance; thema EDItEUR::G Reference

African Principles on the Law Applicable to International Commercial Contracts - Neels, Jan (UJ Press, 2023)
This booklet contains the first draft of the envisaged African Principles on the Law Applicable to International Commercial Contracts. The proposal could be used by national legislators on the continent and African economic integration organisations, particularly the African Union, in, respectively, domestic legislation and regional or supranational laws of a soft or binding nature. The existence of a reliable transnational legal infrastructure in respect of international commercial law, including commercial private international law, is a prerequisite for investor confidence, inclusive economic growth, sustainable development, and the ultimate alleviation of poverty on the African continent. The instrument may contribute to sustainable growth on a long-term basis. The regulation of private international law of contract is essential to the further development of the African Continental Free Trade Area. Jan L Neels is professor of private international law and director of the Research Centre for Private International Law in Emerging Countries at the University of Johannesburg.
Accepted: 2023-11-15T11:31:08Z
Keywords: African principles; International commercial contracts

The International Handbook of Social Enterprise Law: Benefit Corporations and Other Purpose-Driven Companies - Peter, Henry; Vargas Vasserot, Carlos; Alcalde Silva, Jaime (Springer Nature, 2023)
This open-access book brings together international experts who shed new light on the status of social enterprises, benefit corporations and other purpose-driven companies. The respective chapters take a multidisciplinary approach (combining law, philosophy, history, sociology and economics) and provide valuable insights on fostering social entrepreneurship and advancing the common good. In recent years, we have witnessed a significant shift of how business activities are conducted, mainly through the rise of social enterprises. In an effort to target social problems at their roots, social entrepreneurs create organizations that bring transformative social changes by considering, among others, ethical, social, and environmental factors. A variety of social enterprise models are emerging internationally and are proving their vitality and importance. But what does the term “social enterprise” mean? What are its roots? And how does it work in practice within the legal framework of any country? This handbook attempts to answer these questions from a theoretical, historical, and comparative perspective, bringing together 44 contributions written by 71 expert researchers and practitioners in this field. The first part provides an overview of the social enterprise movement, its evolution, and the different forms entities can take to meet global challenges, overcoming the limits of what governments and states can do. The second part focuses on the emergence of benefit corporations and the growing importance of sustainability and societal values, while also analyzing their different legal forms and adaptation to their regulatory environment. In turn, the last part presents the status quo of purpose-driven companies in 36 developed and emerging economies worldwide. This handbook offers food for thought and guidance for everyone interested in this field. It will benefit practitioners and decision-makers involved in social and community organizations, as well as in international development and, more generally speaking, social sciences and economics.
Accepted: 2023-01-20T16:54:44Z
Keywords: B-Corps; BCorp Certification; Benefit Corporations; Business and Management; Business ethics; CSR; Commercial Law; Competencia; Competition law; Corporate Social Responsibility; Finance; Social Business Inititive; Social Enterprises; Social Entrepreneurship

Recueil de textes communautaires sur la libre circulation et le droit d'établissement - Union Economique et Monétaire Ouest Africaine (UEMOA, 2023)